Devic's index case: A critical reappraisal - AQP4-IgG-mediated neuromyelitis optica spectrum disorder, or rather MOG encephalomyelitis? - Jarius, Sven; Wildemann, Brigitte (Journal of the neurological sciences, 2019)
In 1894, Eugène Devic (1858-1930) and his doctoral student Fernand Gault (1873-1936) reported on a patient with optic neuritis (ON) and myelitis and proposed the name “neuro-myélite optique” for this syndrome. Subsequently, Devic became the eponym of neuromyelitis optica (NMO), which was then referred to as “Devic's syndrome”, “Devic's disease” or “Morbus Devic”. Thereby, the case became a historical index case of NMO. For many decades little attention was paid to NMO, which most authors considered a clinical variant of multiple sclerosis. However, the discovery of pathogenic antibodies to aquaporin-4 at the beginning of the 21st century revived interest in the syndrome, and AQP4-IgG-positive NMO spectrum disorders (NMOSD) are now studied as prototypical autoimmune diseases. More recently, antibodies to full-length myelin oligodendrocyte glycoprotein (MOG) have been detected in patients with ON as well as in patients with myelitis, some of whom exhibit a clinical phenotype very similar to that described by Devic. This raises the question of whether Devic's patient might have suffered from MOG encephalomyelitis rather than classic NMOSD. In this article, we summarise and discuss the available evidence for and against that hypothesis. We also discuss differential diagnoses and the question whether Devic's patient, who worked as a hatter and had initially been admitted for nervous hyperexcitability and tremor, might have suffered from co-existing erethism (‘mad hatter disease’), which is caused by chronic occupational exposure to mercury.
Gesehen am 27.01.2020